DEFENSIVE WALLS OF AFRASIAB AND THE MAIN STAGES OF ITS DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
In many multi-layered settlements of Central Asia, and at the Afrasiab settlement, the main attention was paid to the study of defensive walls, since all stages of the development of urban culture were reflected in it. The main goal of this work was to study the most ancient stages of the development of urban culture, comparing it with the material culture of the lower layers, with materials from the Koktepa settlement and other synchronous monuments. As a result of such a comparative analysis, it was established that the urban culture of ancient Samarkand was based on the ancient agricultural culture of the Early Iron Age.